Empowering Micro-Businesses: Unveiling the Catalysts behind Social Media Integration in Indonesia - Nurqamarani, Adisthy Shabrina; Fadilla, Sarah; Priyanto, Agus (Universitas Airlangga, 2024)
Background: An enormous number of micro-businesses in Indonesia have not joined the digital platforms, despite the evident benefits associated with making this transition. One viable avenue for initiating digitalization is through leveraging social media, characterized by its cost-effectiveness and expansive reach to consumers Objective: This study aims to identify the catalyst behind the social media adoption of micro-businesses in the culinary sector in Indonesia Method: This study adopts a qualitative approach, involving interviewing seven micro-businesses owners in Indonesia who were selected through purposive and snowball sampling. Thematic analysis was employed to derive meaningful conclusions. Results: The study’s findings suggest that subjective norms, perceived usefulness, perceived ease of use, perceived behavioral control, competitive pressure, customer demand, and government support hold important roles in the adoption of social media in micro and small businesses. Considering the importance of government support, it can play a pivotal role by providing support and incentives for MSMEs to integrate social media into their operation. Additionally, strategies for positioning businesses in the digital landscape should be developed, keeping customer demand in mind. Conclusion: Leveraging social media presents a cost-effective means for digitalization. This qualitative study unveils the key drivers: subjective norms, perceived usefulness, ease of use, behavioral control, competitive pressure, customer demand, and government support. Government intervention and customer-centric strategies are crucial for successful social media adoption. Keywords: Digital marketing; micro business: social media integration